THE INFLUENCE OF FARMER GROUP PERFORMANCE ON LOWLAND RICE FARMING INCOME IN PASIRAN VILLAGE GEBANG SUB-DISTRICT - Ginting, Adetta Saskia; Hanisah, Hanisah; Mahyuddin, Thursina (AGRIBUSINESS JOURNAL, 2023)
This study aims to analyze the level of performance of farmer groups, income of paddy rice farming and to find out whether the performance of farmer groups affects the income of lowland rice farming in Pasiran Village, Gebang District, Langkat Regency. The sample determination method used in this study was simple random sampling with a total sample of 37 people who were members of the Pasiran Village farmer group. The data used in this study are primary data and secondary data. Primary data was obtained through observation, interviews and questionnaires while secondary data was obtained through journals, books, Agricultural Extension Agency, Gebang District. The data analysis method used in this study is a Likert scale, income analysis and simple linear regression. The results showed that the average score of the performance level of farmer groups was 80.94 , meaning that the performance level of farmer groups was moderate, the average income of lowland rice farming was IDR 2,262,655/planting season and the performance of farmer groups had no effect on lowland rice farming income.